Optical properties of small silver particles embedded in soda-lime silica glasses - Suszyńska, Maria; Morawska-Kowal, Teresa; Krajczyk, Ludwina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The optical characteristics of silver nanoparticles embedded in a surface layer of commercial soda lime silica glass have been analysed. Additional results were obtained by the transmission electron microscopy observations and the selective area electron diffraction patterns. In this report, we have shown the effect of deviation from the spherical shape and non-homogeneous distribution on the optical characteristics of the Ag nanocrystals embedded in the dielectric matrix under study.
Optica Applicata, Vol. 40, 2010, nr 2, s. 397-401
Keywords: optyka; soda-lime silica glass; ion exchange; silver nanoparticles; optical absorption; transmission electron microscopy